2010
DOI: 10.1007/s00421-010-1721-2
|View full text |Cite
|
Sign up to set email alerts
|

Sub-maximal and maximal Yo–Yo intermittent endurance test level 2: heart rate response, reproducibility and application to elite soccer

Abstract: The aims of this study were to (1) determine the reproducibility of sub-maximal and maximal versions of the Yo-Yo intermittent endurance test level 2 (Yo-Yo IE2 test), (2) assess the relationship between the Yo-Yo IE2 test and match performance and (3) quantify the sensitivity of the Yo-Yo IE2 test to detect test-retest changes and discriminate between performance for different playing standards and positions in elite soccer. Elite (n = 148) and sub-elite male (n = 14) soccer players carried out the Yo-Yo IE2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
143
5
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(165 citation statements)
references
References 32 publications
(52 reference statements)
9
143
5
8
Order By: Relevance
“…Heart rate at submaximal intensities is sensitive to changes in maximal performance, and therefore such non-exhaustive testing may be a useful and reliable fitness monitoring tool 9 , especially in season. The findings of the current study identified that the Yo-Yo IR1-sub is reliable assessment method in young elite soccer players, with absolute heart rate at cessation of the 6 minute test (HR6) highlighted as the most reliable metric (ICC = 0.96) ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Heart rate at submaximal intensities is sensitive to changes in maximal performance, and therefore such non-exhaustive testing may be a useful and reliable fitness monitoring tool 9 , especially in season. The findings of the current study identified that the Yo-Yo IR1-sub is reliable assessment method in young elite soccer players, with absolute heart rate at cessation of the 6 minute test (HR6) highlighted as the most reliable metric (ICC = 0.96) ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…8 The Yo-Yo IR1 and Yo-Yo IE2 tests have starting speeds of 10 km.h -1 and 11.5 km.h -1 respectively, with a view of shortening total assessment time, when compared to the slower starting speed (8 km.h -1 ) of the Yo-Yo IE1. The difference in starting speeds between tests result in a broad range of distances covered and total work time, ranging from 2564 ± 554 m during the Yo-Yo IE2, 9 therefore it is difficult to directly compare results due to the methodology applied. Following each 2 × 20 m shuttle, these tests have a rest period of 10 s and 5 s respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large to very large correlations were found between RRST performance vs high-intensity running in the most intense period (r = -0.55-0.74) and during a match (r = -0.55-0.67) for two elite U18 squads playing in the English Premier League and Football League, and one sub-elite U18 squad, respectively. High-intensity running has been shown to have great importance for performance in soccer due to differences between performance level and playing positions (Bradley et al 2009(Bradley et al , 2010Mohr et al 2003), and has been used to validate tests (Bradley et al 2011;Impellizzeri et al 2008;Rampinini et al 2007). However, it has been suggested that rolling, rather than predefined, periods are used when determining specific match intervals because of improved accuracy and a clearer representation of high-intensity distance covered (Varley et al 2012a).…”
Section: Validity Of the Rrstmentioning
confidence: 99%